Influence of access cavity design and use of operating microscope and ultrasonic troughing to detect middle mesial canals in extracted mandibular first molars. (21st July 2020) - Mendes, E. B.; Soares, A. J.; Martins, J. N. R.; Silva, E. J. N. L.; Frozoni, M. R.
Abstract: Aim: To evaluate the influence of various endodontic access cavity designs and the use of an operating microscope (OM) with or without ultrasonic troughing to detect middle mesial canals (MMCs) in extracted mandibular first molars. Methodology: Sixty extracted mandibular first molars were evaluated by cone beam computed tomography (CBCT) in order to detect the presence of MMCs and then divided into two groups ( n  = 30) with an equal proportion of 1 molar with MMC for each 3 molars. A specific access cavity design was performed for each group, either a conservative access cavity (CAC) or a traditional access cavity (TAC). Root canals were detected in three assessment stages: (i) no magnification, (ii) using an OM and (iii) using an OM together with ultrasonic troughing. Evaluations were performed on a mannequin head in an ergonomic working position. The confidence obtained in the assessment stages was portrayed by sensitivity, specificity and accuracy, calculated by the area under the ROC curve. The difference in the proportion of correct diagnoses in identifying the MMC using either CAC or TAC preparation, at each of the three stages, was checked using Cochran's Q tests. Binomial tests were performed at each stage to investigate whether there was a difference between the types of endodontic access designs to detect MMCs. Significance was set at P  < 0.05. Results: Accuracy increased at each assessment stage. At the third stage, both groups provided perfect accuracy (1.00). Cochran's Q tests indicated that the confidence of MMC detection for both TAC and CAC groups ( P  < 0.05) increased significantly at each stage. Binomial tests demonstrated that there was no significant difference between the TAC and CAC groups, when evaluation was performed without magnification ( P  > 0.05), with OM ( P  > 0.05), or with OM associated with ultrasonic troughing ( P  > 0.05). Conclusion: The access cavity design did not significantly affect detection of middle mesial canals in extracted mandibular first molars placed in a mannequin. However, the use of OM increased the accuracy of the MMC identification, especially when associated with ultrasonic troughing.